Project-Based Learning, Process Writing, and Instagram: an Attempt to Enhance the Students' Writing Skill - Dian Arihasta; Yazid Basthomi (Universitas Negeri Malang, 2019)
Abstract: This collaborative classroom action research was aimed to improve the students' ability in writing hortatory exposition text. It involved 30 students of high school as the research subject. Writing test was the instrument used in this study to collect the data. The research findings indicate that the implementation of project-based learning combined with process writing and Instagram could improve the students' writing achievement. The students can improve their average writing score which was higher than the minimum passing score. All of the students were able to increase their writing score by at least 10 points higher compared to which they gained in the initial test. In addition to that, 70% of the students could pass the minimum passing grade. Key Words: project-based learning, process writing, instagram, writing skill Abstrak: Penelitian tindakan kelas kolaboratif ini bertujuan untuk meningkatkan kemampuan siswa dalam menulis teks hortatory exposition. Penelitian ini melibatkan 30 siswa SMA sebagai subjek penelitian. Tes tulis adalah instrumen yang di gunakan untuk pengumpulan data. Hasil penelitian menunjukan penerapan pembelajaran berbasis proyek yang di kombinasikan dengan process writing dan Instagram mampu meningkatkan kemampuan siswa dalam menulis. Semua siswa mampu memperbaiki nilai individu mereka 10 poin lebih baik di bandingkan dengan nilai yang mereka dapat di test awal. Nilai rata-rata siswa juga meningkat di bandingkan dengan nilai yang mereka dapatkan di tes awal. Nilai rata-rata siswa melewati kriteria ketuntasan minimal. Selain itu, 70% siswa mampu mendapatkan nilai lebih baik atau sama dengan kriteria ketuntasan minimal. Kata kunci: pembelajaran berbasis proyek, proses menulis, instagram, keterampilan menulis